Technology in ancient & medieval India - Ray, Aniruddha; Bagchi, S. K. (Sundeep Prakashan, 1986)
Papers presented at the Seminar on Technology in Medieval India--16th to 18th Century, September 7 and 8, 1984, Birla Industrial & Technological Museum, Calcutta.